Shrimp Aquaculture and Social Conflict: Socioeconomic Dynamics in Seliat, East Lombok - Muhammad Izza Mahendra; Abdul Rasyad; Syahrul Amar; Lalu Murdi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This study examines how shrimp-aquaculture expansion shaped socioeconomic change and social conflict in Seliat Hamlet, Menceh Village, East Lombok Regency. It applies a qualitative historical case-study design using in-depth interviews, field observation, village documents, agreement records, and relevant literature. The materials were examined through heuristic source collection, external and internal source criticism, interpretation, historiography, and an interactive qualitative cycle of data condensation, display, and conclusion drawing. The findings show that the farm generated employment, social assistance, and new economic activity for some residents, but benefits were unevenly distributed. Conflict originated in limited community participation, disputed land transactions and unfulfilled promises, reported water and air pollution, declining fishing catches, and weak governmental mediation. It developed vertically between residents, the company, and village authorities, and horizontally between groups supporting and opposing the farm. Protests, petitions, formal complaints, and road blockades became channels of collective mobilization when dialogue forums failed to address substantive grievances. The study argues that aquaculture sustainability cannot be evaluated only through output and investment; it must also include procedural, distributive, and ecological justice. Future governance requires participatory effluent monitoring, a traceable grievance mechanism, independent review of social commitments, impact-based compensation, and an inclusive multi-stakeholder mediation forum.